Post-World War II Rhythm and Blues: Jump Blues, Club Blues, and Roy Brown - Bowman, Rob (Canadian University Music Review / Revue de musique des universités canadiennes, 1996)
The classification of different styles of North American popular music has often been problematic. This paper investigates some of the music referred to as rhythm and blues (r & b) in the late 1940s and early 1950s by specifically looking at the works of one of the music's leading practitioners of the time, Roy Brown. Brown recorded both jump and club blues between 1947 and 1955, placing fifteen records in the Top 20 of the Billboard rhythm and blues charts.For the purposes of this paper fifty-four of the seventy-four songs that Brown recorded in this period were analyzed with respect to structure, performing force, performance style, tempo, arrangement, bass lines, approach to the beat, rate of singing, vocal ornamentation, and lyric content and structure. Three main subdivisions were found within Brown's repertoire, all connected to social behaviour, namely, dance. In the process, a basic biography of Brown is provided and his influence on many subsequent rhythm and blues and rock and roll performers is contextualized.